ANALISIS MAJAS PADA CERITA PENDEK “LOVE IN APPLE” KARYA NURILLAIYAH - Mega Cahyani; Wikanengsih Wikanengsih; Enung Nurhayati (IKIP Siliwangi, 2021)
This research was conducted because it was found in the short story